EVALUATION OF THE EFFECT OF ACRYLIC REMOVABLE DENTURES ON THE IMMUNOMETABOLIC PROFILE AND QUALITY OF LIFE OF PATIENTS - Yanishen, І.V.; Andrienko, К.Yu.; Fedotova, O.L.; Pogorila, A.V.; Khlystun, N.L. (World of Medicine and Biology, 2022)
The purpose of our study was to assess the removable orthopedic constructions impact, made by different methods, on the immunometabolic profile and quality of life of patients in the clinic of orthopedic dentistry. The problem of reducing residual monomers in orthopedic structures has been innovatively solved by developing the technology of their vacuuming using a system of technical means. We included in the study an indicator for assessing the quality of life of patients at all stages of orthopaedic treatment and taking into account the specifics of experiments and the use of questionnaires. Concerning statistically significant changes among patients who used removable orthopedic constructions, the worst results of quality of life before and after treatment were detected in 2N2, using removable dentures which were manufactured by without vacuum method 32.4±0.47 and 92.8±0.35 points, respectively. Despite the fact that the indicators changed 1.27 times in the direction of increase, the final level of quality of life, reflected in the IV stage of orthopedic treatment (6 months after treatment), remained the worst among these patients. Prospects for further research on the use of acrylic base plastics in the treatment of removable dentures are related to the study: the impact of material on the adaptation of the prosthetic area, the impact of structural dental material on the quality of life of patients before treatment with removable orthopedic structures.
Keywords: removable orthopedic constructions; treatment methods; residual monomer; immunometabolic profile; vacuum method; quality of life